Politics or markets: The dual role of the motivation to achieve organizational legitimacy in the development of knowledge management capabilities and business model innovation - Liao, Suqin; Wei, Jingjing; Hu, Qianying (Frontiers in Psychology, 2023)
Build upon institutional theory and knowledge-based view, we seek to investigate how knowledge management capabilities affect the business model innovation by exploring the dual role of different types of legitimation motivations in triggering knowledge management capabilities and moderating the relationship between knowledge management capabilities and business model innovation. The data collected from the 236 Chinese new ventures running their businesses across a variety of sectors The results indicate the both political and market legitimation motivation positively affect knowledge management capabilities. The relationship between knowledge management capabilities and business model innovation are more strongly in high motivation to achieve market legitimacy. However, the positive effect of knowledge management capabilities stimulate business model innovation is more strongly in moderately motivation to achieve political legitimacy than in low or highly political legitimation motivation. The paper has significantly contributed to advancing the body of knowledge of institutional and business model innovation theory and providing deeper insights on the correlation between firm’s motivation to achieve legitimacy and knowledge management capabilities for business model innovations.